Hemispheric differences in the mesostriatal dopaminergic system - Molochnikov, Ilana; Cohen, Dana (Frontiers in Systems Neuroscience, 2014)
The mesostriatal dopaminergic system, which comprises the mesolimbic and the nigrostriatal pathways, plays a major role in neural processing underlying motor and limbic functions. Multiple reports suggest that these processes are influenced by hemispheric differences in striatal dopamine (DA) levels, DA turnover and its receptor activity. Here, we review studies which measured the concentration of DA and its metabolites to examine the relationship between DA imbalance and animal behavior under different conditions. Specifically, we assess evidence in support of endogenous, inter-hemispheric DA imbalance; determine whether the known anatomy provides a suitable substrate for this imbalance; examine the relationship between DA imbalance and animal behavior; and characterize the symmetry of the observed inter-hemispheric laterality in the nigrostriatal and the mesolimbic DA systems. We conclude that many studies provide supporting evidence for the occurrence of experience-dependent endogenous DA imbalance which is controlled by a dedicated regulatory/compensatory mechanism. Additionally, it seems that the link between DA imbalance and animal behavior is better characterized in the nigrostriatal than in the mesolimbic system. Nonetheless, a variety of brain and behavioral manipulations demonstrate that the nigrostriatal system displays symmetrical laterality whereas the mesolimbic system displays asymmetrical laterality which supports hemispheric specialization in rodents. The reciprocity of the relationship between DA imbalance and animal behavior (i.e. the capacity of animal training to alter DA imbalance for prolonged time periods) remains controversial, however, if confirmed, may provide a valuable noninvasive therapeutic means for treating abnormal DA imbalance.